Criminal Law Politics Against Corruption Criminal Acts Through Hand-Catching Operation - Ismaidar Ismaidar; Tamaulina Br Sembiring; Majidah Pohan (International Journal of Sociology and Law, 2025)
As a system, the law will run well when the system is connected and working actively. The practice of criminal acts of corruption that occurs in Indonesia is increasingly sophisticated, systematic and widespread at all levels of society which has an impact on the amount of state financial losses. Various statutory regulations have been attempted to eradicate corruption, namely Law Number 31 of 1999 jo. Law Number 20 of 2001 and the Government has even ratified several articles of the 2003 United Nations Convention Against Corruption (UNCAC) through Law Number 7 of 2006. However, to date it is still unable and effective to enforce it in eradicating corruption. The Corruption Eradication Commission (KPK) has a system for dealing with corruption cases, namely Operation Arrest (OTT). anywhere in Indonesia. The type of research applied is normative legal research with a normative juridical approach, namely research carried out based on library materials which are secondary data. Based on the results of the research, it can be stated that in the politics of criminal law in dealing with criminal acts of corruption based on penal and non-penal policies, it is no longer effective in eradicating criminal acts of corruption which are detrimental to the country's finances and economy and the Corruption Eradication Commission's policy, which is included in one of its policies, is carrying out Hand Catch Operations, namely tapping. Tapping is the activity of listening, recording, deflecting, changing, inhibiting and recording the transmission of electronic information or electronic documents, whether using communication cable networks or wireless networks, such as electromagnetic radiation or radio frequency, including examining packages, postal mail, correspondence and other documents. Apart from that, the legal politics of dealing with criminal acts of corruption through Operation Capture of Arms, including the lack of regulations regarding wiretapping and entrapment carried out by the Corruption Eradication Commission, is vulnerable to violations of Human Rights (HAM), especially regarding entrapment, because entrapment is not recognized by law or as a criminal act. corruption in Indonesia.